2021
DOI: 10.18502/jmehm.v14i6.6750
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Indonesian medical students of ethical issues during their clinical clerkship in a rural setting

Abstract: Although ethics is an essential part of medical education, little attention has been paid to ethics education during the clerkship phase, where medical students observe how physicians make decisions regarding various ethical problems. Specific nuances and cultural contexts such as working in a rural setting can determine ethical issues raised. This phenomenology study aimed to explore ethical issues experienced by Indonesian students during clinical clerkship in a rural setting. In-depth interviews were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Given this context, the concept of animal ethics no longer exists only for scientists but should also be introduced to a wider audience, such as university students [ 7 ]. This approach aligns with the recognition that ethics, including animal ethics, is an essential part of medical education [ 8 , 9 ]. Implementing the 3R principles in laboratory animal ethics education will enhance medical students' ethical standards and practical skills in designing and conducting experiments.…”
Section: Introductionmentioning
confidence: 91%
“…Given this context, the concept of animal ethics no longer exists only for scientists but should also be introduced to a wider audience, such as university students [ 7 ]. This approach aligns with the recognition that ethics, including animal ethics, is an essential part of medical education [ 8 , 9 ]. Implementing the 3R principles in laboratory animal ethics education will enhance medical students' ethical standards and practical skills in designing and conducting experiments.…”
Section: Introductionmentioning
confidence: 91%
“…11 Another research regarding ethical problems present in rural areas of Indonesia revealed that scarce healthcare facilities and limitations to healthcare availability gave rise to various ethical issues concerning lack of privacy, consent, and limited facilities and resources. 12 Furthermore, a research paper on health ethics in six South-East Asia Region countries such as Bangladesh, Indonesia, India, Nepal, Myanmar, and Sri Lanka highlighted ethical issues arising due to a lack of patients' informed consent and resources not allowing patients to get specialty health treatment. Issues related to medical termination of pregnancy, and female foeticide were also present in India due to illegal abortions and the influence of different ethnicities and multiple gods on medical treatments.…”
Section: Reviewmentioning
confidence: 99%